The potential of the South African plant Tulbaghia Violacea Harv for the treatment of triple negative breast cancer - Mohammed Alaouna; Thulo Molefi; Richard Khanyile; Nkhensani Chauke-Malinga; Aristotelis Chatziioannou; Thifhelimbilu Emmanuel Luvhengo; Maropeng Raletsena; Clement Penny; Rodney Hull; Zodwa Dlamini (Scientific Reports)
Abstract Triple-negative breast cancer (TNBC) is difficult to treat and has a low five-year survival rate. In South Africa, a large percentage of the population still relies on traditional plant-based medicine. To establish the utility of both methanol and water-soluble extracts from the leaves of Tulbaghia violacea, cytotoxicity assays were carried out to establish the IC50 values against a TNBC cell line. Cell cycle and apoptosis assays were carried out using the extracts. To identify the molecular compounds, present in water-soluble leaf extracts, NMR spectroscopy was performed. Compounds of interest were then used in computational docking studies with the anti-apoptotic protein COX-2. The IC50 values for the water- and methanol-soluble extracts were determined to be 400 and 820 µg/mL, respectively. The water-soluble extract induced apoptosis in the TNBC cell line to a greater extent than in the normal cell line. RNAseq indicated that there was an increase in the transcription of pro-apoptotic genes in the TNBC cell line. The crude extract also caused these cells to stall in the S phase. Of the 61 compounds identified in this extract, five demonstrated a high binding affinity for COX-2. Based on these findings, the compounds within the extract show significant potential for further investigation as candidates for the development of cancer therapeutics, particularly for TNBC.